The dreamer and the doctor : a forest lover and a physician on the edge of the frontier - Nisbet, Jack, 1949- (Sasquatch Books, 2018)
"Dr. Carrie Leiberg, a pioneer physician, fought hard for public health while nurturing both a troubled son and a fruit orchard. Her husband, John Leiberg, was a Swedish immigrant and self-taught naturalist who transformed himself from pickax Idaho prospector to special field agent for the US Forest Commission and warned Washington DC of ecological devastation of public lands. The Leiberg story opens a window into the human and natural landscape of a century past that reflects all the thorny issues of our present time"--